Corporate Governance, Profitabilitas, Size, Growth, dan Nilai Perusahaan - Azhar Latief; Fenty Fauziah (Politeknik Ganesha Medan, 2023)
The purpose of this research is to test and analyze the effect of profitability as measured by ROA, size as measured by total assets, and growth as measured by asset growth on firm value as measured by Tobin's Q; to test and analyze how corporate governance as measured by the CGPI scores moderates the effect of profitability, size, and growth on firm value. Data used in this research is secondary data. There is 302 population used in this research which is companies were included in the CGPI rating in period 2011-2019 (pooled data). There are 45 samples selected by using the purposive sampling method. The data analysis technique used is PLS-SEM. This research showed that profitability has a significant positive effect on firm value, size has a significant positive effect on firm value, growth hasn't a significant effect on firm value. Corporate governance hasn't moderated the effect of profitability on firm value, corporate governance has strengthened the effect of size on firm value, and corporate governance hasn't moderated the effect of growth on firm value.